Multilateral Boundary Spanners: Creating Virtuous Cycles in the Development of Health Care Networks. (December 2015) - Patru, Daniela; Lauche, Kristina; van Kranenburg, Hans; Ziggers, Gerrit Willem
Understanding how health care networks achieve their goals is critical for managers and researchers alike. Our study addresses this issue by applying qualitative methods to retrospectively study the involvement of boundary spanners in the setup and implementation of a health care network in the Netherlands. We found that boundary spanners who acted multilaterally, that is, both within and across organizations, could successfully represent their organizations' interests at the network level and implement the required intraorganizational developments. By acting multilaterally, these boundary spanners generated virtuous cycles in the development of the network, whereby their successful actions supported the actions of their subordinates in setting up and implementing network agreements. In contrast, boundary spanners who had not been acting multilaterally before the network's kickoff were insufficiently prepared to enact their network-related tasks, and only successfully did so once they began operating both within and across organizations.